HOW TO SIMPLIFY SIN4X+COS4X USING TRIGONOMETRICAL IDENTITIES?

     
$sin^4x+cos^4x$I should rewrite this expression into a new khung to plot the function.

Bạn đang xem: How to simplify sin4x+cos4x using trigonometrical identities?

eginalign& = (sin^2x)(sin^2x) - (cos^2x)(cos^2x) \& = (sin^2x)^2 - (cos^2x)^2 \& = (sin^2x - cos^2x)(sin^2x + cos^2x) \& = (sin^2x - cos^2x)(1) longrightarrow,= sin^2x - cos^2xendalign

Is that true?


*

*

eginalignsin^4 x +cos^4 x&=sin^4 x +2sin^2xcos^2 x+cos^4 x - 2sin^2xcos^2 x\&=(sin^2x+cos^2 x)^2-2sin^2xcos^2 x\&=1^2-frac12(2sin xcos x)^2\&=1-frac12sin^2 (2x)\&=1-frac12left(frac1-cos 4x2 ight)\&=frac34+frac14cos 4xendalign


*

Let $$displaystyle y=sin^4 x+cos^4 x = left(sin^2 x+cos^2 x ight)^2-2sin^2 xcdot cos^2 x = 1-frac12left(2sin xcdot cos x ight)^2$$

Now using $$ sin 2A = 2sin Acos A$$

So, we get $$displaystyle y=1-frac12sin^2 2x$$


*

*

Note that $a^2 + b^2 = (a+b)^2 - 2ab$

$$(sin^2 x)^2 + (cos^2 x)^2 = (sin^2 x + cos^2 x)^2 - 2sin^2 xcos^2 x =(sin^2 x + cos^2 x)^2 - 2(sin xcos x)^2 = \ 1 -frac sin^2 2x2$$

Note the following results:

$$ sin^2 x + cos^2 x = 1$$

$$ sin x cos x = fracsin 2x2$$


Expand in terms of complex exponentials.

$$sin^4 x + cos^4 x = left( frace^ix - e^-ix2i ight)^4 + left( frace^ix + e^-ix2 ight)^4$$

Notice that $i^4 = +1$, so we get

$$sin^4 x + cos^4 x = frac116 left( 2e^4ix + 2 e^-4ix + 12 ight)$$

where we use the relation $(a+b)^4 = a^4 + 4 a^3 b + 6 a^2 b^2 + 4 ab^3 + b^4$. The terms of the size $a^3 b$ & $ab^3$ all cancel by addition.

Xem thêm: Bài Văn Mẫu Lớp 9: Thuyết Minh Về Một Cuốn Sách Mà Em Yêu Thích

This leaves us with a final result:

$$sin^4 x + cos^4 x = frac416 left(frace^4ix + e^-4ix2 ight) + frac1216 = frac34 + frac14 cos 4x$$


nội dung
Cite
Follow
answered Sep 30, 2015 at 17:14
MuphridMuphrid
19.1k11 gold badge2727 silver badges5757 bronze badges
$endgroup$
add a comment |
1
$egingroup$
If you want khổng lồ express in functions of higher frequencies lượt thích this $$sum_k=0^N sin(kx) + cos(kx)$$ Then you can use the Fourier transform together with convolution theorem. This will work out for any sum of powers of cos and sin, even $sin^666(x)$.


share
Cite
Follow
answered Sep 30, 2015 at 17:09
depsangtrong.comreadlerdepsangtrong.comreadler
24.7k99 gold badges3333 silver badges8585 bronze badges
$endgroup$
địa chỉ a bình luận |

You must log in to answer this question.


Not the answer you're looking for? Browse other questions tagged .
Featured on Meta
Linked
8
Deriving an expression for $cos^4 x + sin^4 x$
0
Find $int_0^2pi frac1sin^4x + cos^4x dx$.

Xem thêm: Phép Dịch " Phòng Bệnh Hơn Chữa Bệnh Tiếng Anh, Prevention Is Better Than Cure


Related
1
Trigonometric Identities: $fracsin^2 heta1+cos heta=1-cos heta$
2
Simplifying second derivative using trigonometric identities
1
Simplify $-2sin(x)cos(x)-2cos(x)$
0
Simplify the expression & leave answer in terms of $sin x$ and/or $cos x$
0
How can we bound $fracsin( heta)cos( heta)sin( heta)$
1
Minimum value of $cos^2 heta-6sin heta cos heta+3sin^2 heta+2$
1
Transforming the equation $cot x -cos x = 0$ into the khung $cos x(1- sin x) = 0$
1
Simplify: $fracsin(3x-y)-sin(3y-x)cos(2x)+cos(2y) $
3
Simplify trigonometric expression using trigonometric identities
Hot Network Questions more hot questions

Question feed
Subscribe to RSS
Question feed to subscribe to this RSS feed, copy và paste this URL into your RSS reader.


depsangtrong.comematics
Company
Stack Exchange Network
Site kiến thiết / hình ảnh sản phẩm © 2022 Stack Exchange Inc; user contributions licensed under CC BY-SA. Rev2022.12.21.43127


Your privacy

By clicking “Accept all cookies”, you agree Stack Exchange can store cookies on your device và disclose information in accordance with our Cookie Policy.